A high-strength wear-resistant composite material and its preparation method and application
By using glass fibers with nanozirconia-loaded surfaces as modified fiber composite reinforcement, the problem of poor performance in mechanical and mechanical properties of composite materials is solved, and higher mechanical strength and wear resistance are achieved, which is suitable for applications with high performance needs such as machine tools.
Patent Information
- Application Number
- CN202411845916.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-16
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2044-12-16
AI Technical Summary
The existing composite materials have poor performance in mechanical and mechanical properties, cannot meet the high strength requirements of the machine tool, and there are interface problems between the glue and filler.
Glass fibers with nanozirconia on the surface are used as the modified fiber composite reinforcement material, and glass short fibers are modified by bridge reagent and nanozirconia is solid to improve the interface connection force between the glue and filler.
The mechanical strength and wear resistance of composite materials are improved, so that they can more effectively meet the high strength and wear resistance requirements of machine tools.
Smart Images

Figure CN119306423B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of composite materials, and in particular to a high-strength wear-resistant composite material and a preparation method and application thereof. Background Art
[0002] As one of the core equipment in modern industry, the performance of machine tools directly determines the accuracy and efficiency of machined parts. As key components of machine tools, machine tool bed guides and base guide parts have extremely high requirements for their materials. They not only need to have high strength and high wear resistance, but also good oil resistance, acid and alkali resistance and thermal stability. At present, the bed, base and other parts of machine tools are mainly made by welding metal castings. This type of metal casting is heavy, inconvenient to install and transport, and has great difficulties in practical application. Therefore, the development of new composite materials to replace traditional metal materials is of great significance to the long-term development of machine tools.
[0003] Composite materials are generally composed of two parts: adhesive and filler. The adhesive is generally composed of a polymer material such as epoxy resin and a curing agent, and the filler can generally be sand, stone, etc. Since composite materials can have the common characteristics of both, they are more advantageous than simple polymer materials or inorganic materials. However, the adhesive and filler themselves are two substances in different phases, and there are certain interface problems between them. Therefore, their performance in mechanical properties is relatively poor and cannot meet the high strength requirements of machine tools. Based on this, the present invention provides a high-strength wear-resistant composite material that can solve the problems existing in the prior art. Summary of the invention
[0004] 1. Technical issues to be resolved
[0005] In view of the deficiencies in the prior art, the present invention provides a high-strength wear-resistant composite material and a preparation method and application thereof.
[0006] (II) Technical solution
[0007] A high-strength wear-resistant composite material, comprising the following raw materials in parts by weight:
[0008] 50-60 parts of coarse aggregate;
[0009] 40-50 parts of fine aggregate;
[0010] 3-6 parts of modified fiber composite reinforcement;
[0011] Epoxy resin 20-35 parts;
[0012] 5-15 parts of curing agent;
[0013] Defoaming agent 0.5-1.5 parts;
[0014] 5-10 parts of filler.
[0015] As a further solution of the present invention, the coarse aggregate is selected from crushed stone with a particle size of 10-15 mm; the fine aggregate is selected from machine-made sand or river sand with a particle size of ≤5 mm.
[0016] As a further embodiment of the present invention, the preparation method of the modified fiber composite reinforcement is as follows:
[0017] The glass short fibers are ultrasonically dispersed in an ethanol aqueous solution with a volume fraction of 60-70% to form a uniform dispersion, and then a bridging agent is added. After the addition is completed, the heating rate is controlled to be 2-4°C / min, the temperature is raised to 60-70°C, and the heat treatment is carried out for 2-4 hours. Then the temperature is lowered to 50-55°C, and nano-zirconium oxide is continuously added, and ultrasonic dispersion is carried out for 20-30 minutes. Then the temperature is raised to 70-80°C, and the heat treatment is carried out for 4-8 hours. Then the material is cooled and discharged, and the solid material is separated. After washing and drying, the modified fiber composite reinforcement material can be obtained.
[0018] In the above technical scheme, the surface of the glass short fiber is first modified using a bridging agent, and then the nano-zirconium oxide is immobilized using the silanol groups produced by hydrolysis of the remaining siloxane groups in the bridging agent structure to obtain glass fiber with nano-zirconium oxide loaded on the surface, that is, a modified fiber composite reinforcement.
[0019] As a further embodiment of the present invention, the preparation method of the bridging reagent is as follows:
[0020] Step 1: Add a halogenated silane coupling agent and diethanolamine to anhydrous toluene, stir evenly after adding, raise the temperature to 60-70°C under nitrogen protection, keep the temperature for reaction for 2-4 hours, evaporate and remove the solvent, collect the product, and obtain a silane intermediate;
[0021] Step 2: Add the silane intermediate to N,N-dimethylformamide, stir evenly, pour into a polymerization kettle, introduce nitrogen protection, and then add 9,9-bis(3,4-dicarboxyphenyl)fluorene anhydride and a catalyst to the polymerization kettle under stirring. After the addition, raise the temperature to 60-80°C, continue stirring and keep warm for 8-12 hours, evaporate the solvent, cool and discharge the material, and the bridging reagent can be obtained.
[0022] As a further embodiment of the present invention, in step 1, the halogenated silane coupling agent is any one of 3-chloropropyltrimethoxysilane, 3-chloropropyltriethoxysilane, 3-bromopropyltrimethoxysilane or 3-bromopropyltriethoxysilane.
[0023] As a further embodiment of the present invention, in step 2, the catalyst is boron trifluoride ether complex or p-toluenesulfonic acid.
[0024] As a further solution of the present invention, the mass ratio of the short glass fiber to the nano-zirconia is 1:0.1-0.2.
[0025] In the above technical scheme, a halogenated silane coupling agent and diethanolamine are first used as reactants, and a silane derivative containing two equivalents of active hydroxyl substituents in the structure, i.e., a silane intermediate, is obtained through a substitution reaction. Then, by using a catalyst for catalysis, the hydroxyl substituents in the silane intermediate structure can be continuously and uninterruptedly subjected to ring-opening esterification condensation with the anhydride substituents in the 9,9-bis(3,4-dicarboxyphenyl)fluorene dianhydride structure, thereby forming an alternatingly connected macromolecular polymer, i.e., a bridging agent.
[0026] As a further embodiment of the present invention, the epoxy resin is bisphenol A epoxy resin; the curing agent is an acid anhydride curing agent; the defoaming agent is polyether modified polysiloxane; and the filler is any one of fumed silica, talc, calcium titanate or titanium dioxide.
[0027] A method for preparing a high-strength wear-resistant composite material comprises the following steps:
[0028] The first step is to weigh each raw material according to the weight and set aside;
[0029] Step 2: Add the coarse aggregate, fine aggregate, modified fiber composite reinforcement and filler into the epoxy resin, and mechanically stir and mix them at a stirring rate of 300-500 r / min for 10-20 minutes to form a precursor material;
[0030] Step 3: Adjust the speed to 100-200r / min, then add defoamer to the precursor, stir for 30-60min, stop stirring, let stand to defoam, and form a mixture;
[0031] Step 4: Add the curing agent to the mixture, stir evenly, then pour into the mold, vibrate and compact it, and after it is completely cured, demould it to obtain a composite material.
[0032] An application of a high-strength wear-resistant composite material, wherein the high-strength wear-resistant composite material is applied to a machine tool.
[0033] 3. Beneficial technical effects
[0034] The present invention is to prepare a glass fiber with nano zirconium oxide loaded on the surface as a modified fiber composite reinforcement. First, since a large amount of rigid benzene ring structures are contained in the bridging agent structure connecting the nano zirconium oxide and the glass fiber, π-π conjugation can be produced with the epoxy resin, so that the modified fiber composite reinforcement can have a good interface connection force with the glue epoxy resin. At the same time, there are also a large number of siloxane groups that are not involved in the reaction in the bridging agent structure, which can also produce good interactions with the coarse aggregate, fine aggregate, etc. in the composite material. Therefore, the modified fiber composite reinforcement can act as a compatibilizer between the glue and the filler, so that a good interface bonding force can be produced between each other, and then the composite material can show more excellent mechanical strength, and this kind of connection structure can actually make the reinforcing advantage of the glass fiber effectively play, and further enhance the mechanical properties of the composite material. In addition, the nano zirconium oxide is fixed on the surface of the glass fiber, and can produce a slight slip, forming a ball effect, so the wear resistance of the composite material can also be improved. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings required for describing the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other accompanying drawings can be obtained based on these accompanying drawings without paying creative work.
[0036] Figure 1 This is the infrared test image of the bridging reagent. DETAILED DESCRIPTION
[0037] In order to facilitate the understanding of the present invention, the present invention will be described more fully below. Preferred embodiments of the present invention are given below. However, the present invention can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the understanding of the disclosure of the present invention more thorough and comprehensive.
[0038] Preparation Example 1
[0039] Preparation of modified fiber composite reinforcement:
[0040] 3g of glass short fiber was ultrasonically dispersed in a 70% ethanol aqueous solution by volume to form a uniform dispersion, and then 0.5g of a bridging agent was added. After the addition, the heating rate was controlled to be 2°C / min, the temperature was raised to 70°C, and the mixture was kept warm for 3h. Then the temperature was lowered to 50°C, and 0.4g of nano-zirconium oxide was added, and the mixture was ultrasonically dispersed for 30min. The temperature was then raised to 80°C, and the mixture was kept warm and stirred for 6h. Then the temperature was lowered and the solid material was separated. After washing and drying, a modified fiber composite reinforcement material was obtained.
[0041] The preparation method of the bridging reagent is as follows:
[0042] Step 1: Add 1.2 g of 3-chloropropyltriethoxysilane and 0.5 g of diethanolamine to anhydrous toluene. After the addition, stir evenly. Under nitrogen protection, raise the temperature to 65° C., keep the temperature for 3 hours, evaporate the solvent, collect the product, and obtain a silane intermediate.
[0043] Step 2: Add 0.6 g of silane intermediate to N,N-dimethylformamide, stir evenly, pour into a polymerization kettle, introduce nitrogen protection, and then add 0.9 g of 9,9-bis(3,4-dicarboxyphenyl)fluorene anhydride and 0.01 g of p-toluenesulfonic acid to the polymerization kettle under stirring. After the addition, raise the temperature to 70°C, continue stirring and keep warm for 9 hours, evaporate the solvent, cool and discharge the material, and the bridging reagent can be obtained.
[0044] Figure 1 This is the infrared test image of the bridging reagent, where 3000cm -1 ~3100cm -1 The characteristic absorption peak at 1781cm is the characteristic absorption peak of carbon and hydrogen on the benzene ring skeleton. -1 The characteristic absorption peak at 1734 cm is the characteristic absorption peak of the ester group C=O produced by the ring-opening esterification reaction. -1 The characteristic absorption peak at 1089 cm is the characteristic absorption peak of carboxyl C=O produced by the ring-opening esterification reaction. -1 The characteristic absorption peak at is the characteristic absorption peak of silicon-oxygen bond.
[0045] Example 1
[0046] A high-strength wear-resistant composite material, comprising the following raw materials in parts by weight:
[0047] 50 parts of coarse aggregate;
[0048] 40 parts of fine aggregate;
[0049] 3 parts of modified fiber composite reinforcement;
[0050] Epoxy resin 20 parts;
[0051] 5 parts of tetrahydrophthalic anhydride;
[0052] 0.5 parts of polyether modified polysiloxane;
[0053] 5 parts of fumed silica.
[0054] The preparation method of the composite material comprises the following steps:
[0055] The first step is to weigh each raw material according to the weight and set aside;
[0056] Step 2: Add the coarse aggregate, fine aggregate, modified fiber composite reinforcement and fumed silica into the epoxy resin, and mechanically stir and mix at a stirring rate of 300 r / min for 20 minutes to form a precursor material;
[0057] Step 3: Adjust the speed to 100r / min, then add polyether-modified polysiloxane to the precursor, stir for 60min, stop stirring, let stand to defoam, and form a mixture;
[0058] Step 4: Add tetrahydrophthalic anhydride to the mixture, stir evenly, then pour into a mold, vibrate and compact it, and after it is completely solidified, demould it to obtain a composite material.
[0059] The coarse aggregate is selected from crushed stone with a particle size of 10-15 mm; the fine aggregate is selected from river sand with a particle size of ≤5 mm; the preparation method of the modified fiber composite reinforcement is shown in Preparation Example 1; the epoxy resin is selected from E51 epoxy resin, and the following are the same.
[0060] Example 2
[0061] A high-strength wear-resistant composite material, comprising the following raw materials in parts by weight:
[0062] 55 parts of coarse aggregate;
[0063] 45 parts of fine aggregate;
[0064] 5 parts of modified fiber composite reinforcement;
[0065] Epoxy resin 25 parts;
[0066] 6 parts of tetrahydrophthalic anhydride;
[0067] 1 part of polyether modified polysiloxane;
[0068] 6 parts of talcum powder.
[0069] The preparation method of the composite material comprises the following steps:
[0070] The first step is to weigh each raw material according to the weight and set aside;
[0071] Step 2: Add the coarse aggregate, fine aggregate, modified fiber composite reinforcement and talcum powder into the epoxy resin, and mechanically stir and mix at a stirring rate of 400 r / min for 20 minutes to form a precursor material;
[0072] Step 3: Adjust the speed to 150r / min, then add polyether-modified polysiloxane to the precursor, stir for 40 minutes, stop stirring, let stand to defoam, and form a mixture;
[0073] Step 4: Add tetrahydrophthalic anhydride to the mixture, stir evenly, then pour into a mold, vibrate and compact it, and after it is completely solidified, demould it to obtain a composite material.
[0074] Example 3
[0075] A high-strength wear-resistant composite material, comprising the following raw materials in parts by weight:
[0076] 60 parts of coarse aggregate;
[0077] 50 parts of fine aggregate;
[0078] 6 parts of modified fiber composite reinforcement;
[0079] Epoxy resin 35 parts;
[0080] 15 parts of tetrahydrophthalic anhydride;
[0081] 1.5 parts of polyether modified polysiloxane;
[0082] 10 parts of titanium dioxide.
[0083] The preparation method of the composite material comprises the following steps:
[0084] The first step is to weigh each raw material according to the weight and set aside;
[0085] Step 2: Add coarse aggregate, fine aggregate, modified fiber composite reinforcement and titanium dioxide into epoxy resin, and mechanically stir and mix at a stirring rate of 500 r / min for 10 minutes to form a precursor material;
[0086] Step 3: Adjust the speed to 200r / min, then add polyether-modified polysiloxane to the precursor, stir for 30 minutes, stop stirring, let stand to defoam, and form a mixture;
[0087] Step 4: Add tetrahydrophthalic anhydride to the mixture, stir evenly, then pour into a mold, vibrate and compact it, and after it is completely solidified, demould it to obtain a composite material.
[0088] Comparative Example 1
[0089] A high-strength wear-resistant composite material, comprising the following raw materials in parts by weight:
[0090] 55 parts of coarse aggregate;
[0091] 45 parts of fine aggregate;
[0092] 5 parts of glass short fiber;
[0093] Epoxy resin 25 parts;
[0094] 6 parts of tetrahydrophthalic anhydride;
[0095] 1 part of polyether modified polysiloxane;
[0096] 6 parts of talcum powder.
[0097] The preparation method of the composite material comprises the following steps:
[0098] The first step is to weigh each raw material according to the weight and set aside;
[0099] Step 2: Add coarse aggregate, fine aggregate, short glass fiber and talcum powder into epoxy resin, and mechanically stir and mix at a stirring rate of 400 r / min for 20 minutes to form a precursor material;
[0100] Step 3: Adjust the speed to 150r / min, then add polyether-modified polysiloxane to the precursor, stir for 40 minutes, stop stirring, let stand to defoam, and form a mixture;
[0101] Step 4: Add tetrahydrophthalic anhydride to the mixture, stir evenly, then pour into a mold, vibrate and compact it, and after it is completely solidified, demould it to obtain a composite material.
[0102] Comparative Example 2
[0103] A high-strength wear-resistant composite material, comprising the following raw materials in parts by weight:
[0104] 55 parts of coarse aggregate;
[0105] 45 parts of fine aggregate;
[0106] Epoxy resin 25 parts;
[0107] 6 parts of tetrahydrophthalic anhydride;
[0108] 1 part of polyether modified polysiloxane;
[0109] 6 parts of talcum powder.
[0110] The preparation method of the composite material comprises the following steps:
[0111] The first step is to weigh each raw material according to the weight and set aside;
[0112] Step 2: Add coarse aggregate, fine aggregate and talcum powder into epoxy resin, and mechanically stir and mix at a stirring rate of 400 r / min for 20 minutes to form a precursor material;
[0113] Step 3: Adjust the speed to 150r / min, then add polyether-modified polysiloxane to the precursor, stir for 40 minutes, stop stirring, let stand to defoam, and form a mixture;
[0114] Step 4: Add tetrahydrophthalic anhydride to the mixture, stir evenly, then pour into a mold, vibrate and compact it, and after it is completely solidified, demould it to obtain a composite material.
[0115] Test Case
[0116] The composite materials in the embodiments and comparative examples were tested for performance, and the results are recorded in Table 1:
[0117] Table 1 - Test results
[0118] The compressive strength and tensile strength test methods refer to the standard GB / T 2567-2021;
[0119] The test method for the wear amount is as follows: a block sample of the composite material with a specification of 20cm×20cm×10mm is placed on a grinding rotation test table, the rotation speed is set to (50±2)r / min, the load is 1000g, and the grinding wheel is SC10. The friction test is carried out, and the wear amount of the test sample is measured after 5000 revolutions. The specific method refers to the standard ASTM D3884.
[0120] From the analysis of the test results, it can be seen that the use of the modified fiber composite reinforcement in Preparation Example 1 as an additive can make the prepared composite material show more excellent mechanical properties. After using unmodified short glass fibers as additives, the mechanical strength of the composite material is obviously reduced. This is due to the interface problems between the components in the composite material. The short glass fibers are also difficult to effectively play their own advantages in this environment. After the short glass fibers are directly removed, the advantages of the glass fibers cannot be utilized, resulting in a further reduction in the mechanical properties of the material.
[0121] Based on the ideal embodiment of the present invention, through the above description, relevant personnel can make various changes and modifications without departing from the technical concept of the present invention. The technical scope of the present invention is not limited to the content in the specification, and the technical scope must be determined according to the scope of the claims.
Claims
1. A high-strength wear-resistant composite material, characterized in that: The following raw materials are included in parts by weight: 50-60 parts of coarse aggregate; 40-50 parts of fine aggregate; 3-6 parts of modified fiber composite reinforcement; Epoxy resin 20-35 parts; 5-15 parts of curing agent; Defoaming agent 0.5-1.5 parts; 5-10 parts of filler; The preparation method of the modified fiber composite reinforcement is as follows: The glass short fiber is ultrasonically dispersed in an ethanol aqueous solution with a volume fraction of 60-70% to form a uniform dispersion, and then a bridging agent is added. After the addition is completed, the heating rate is controlled to be 2-4°C / min, the temperature is raised to 60-70°C, and the temperature is kept warm for 2-4 hours, and then the temperature is lowered to 50-55°C, and nano zirconium oxide is continuously added, and ultrasonic dispersion is performed for 20-30 minutes. The temperature is then raised to 70-80°C, and the temperature is kept warm and stirred for 4-8 hours, and then the material is cooled and discharged, and the solid material is separated. After washing and drying, the modified fiber composite reinforcement material can be obtained; The preparation method of the bridging reagent is as follows: Step 1: Add a halogenated silane coupling agent and diethanolamine to anhydrous toluene, stir evenly after adding, raise the temperature to 60-70°C under nitrogen protection, keep the temperature for reaction for 2-4 hours, evaporate and remove the solvent, collect the product, and obtain a silane intermediate; Step 2: Add the silane intermediate to N,N-dimethylformamide, stir evenly, pour into a polymerization kettle, introduce nitrogen protection, and then add 9,9-bis(3,4-dicarboxyphenyl)fluorene anhydride and a catalyst to the polymerization kettle under stirring. After the addition, raise the temperature to 60-80°C, continue stirring and heat preservation for 8-12 hours, evaporate the solvent, cool and discharge the material, and the bridging reagent can be obtained; The halogenated silane coupling agent is any one of 3-chloropropyltrimethoxysilane, 3-chloropropyltriethoxysilane, 3-bromopropyltrimethoxysilane or 3-bromopropyltriethoxysilane; The catalyst is boron trifluoride ether complex or p-toluenesulfonic acid.
2. A high-strength wear-resistant composite material according to claim 1, characterized in that: The coarse aggregate is selected from crushed stone with a particle size of 10-15 mm; the fine aggregate is selected from machine-made sand or river sand with a particle size of ≤5 mm.
3. The high-strength wear-resistant composite material according to claim 1, characterized in that: The mass ratio of the short glass fibers to the nano-zirconia is 1:0.1-0.
2.
4. The high-strength wear-resistant composite material according to claim 1, characterized in that: The epoxy resin is bisphenol A epoxy resin; the curing agent is an acid anhydride curing agent; the defoaming agent is polyether-modified polysiloxane; and the filler is any one of fumed silica, talcum powder, calcium titanate or titanium dioxide.
5. A method for preparing the high-strength wear-resistant composite material according to claim 1, characterized in that: The following steps are involved: The first step is to weigh each raw material according to the weight and set aside; Step 2: Add the coarse aggregate, fine aggregate, modified fiber composite reinforcement and filler into the epoxy resin, and mechanically stir and mix at a stirring rate of 300-500 r / min for 10-20 minutes to form a precursor material; Step 3: Adjust the speed to 100-200r / min, then add defoamer to the precursor, stir for 30-60min, stop stirring, let stand to defoam, and form a mixture; Step 4: Add the curing agent to the mixture, stir evenly, then pour into the mold, vibrate and compact it, and after it is completely cured, demould it to obtain a composite material.
6. An application of the high-strength wear-resistant composite material as claimed in claim 1, characterized in that: The high-strength wear-resistant composite material is applied to machine tools.
Citation Information
Patent Citations
Preparation method of fiber / ZrO2 aerogel composite material
CN102503355A
Ultra-wearproof epoxy precast slab and installation method thereof
CN102826791A